Chikungunya virus infection in Cynomolgus macaques following Intradermal and aerosol exposure - Chris M. Cirimotich (Virology Journal, 2017)
Abstract Background Chikungunya virus (CHIKV) is transmitted via mosquito bite and potentially by aerosol, causing chikungunya fever and arthritic disease in humans. There are currently no licensed vaccines or antiviral therapeutics to protect against CHIKV infection in humans. Animal models recapitulating human disease, especially for transmission by aerosol, are needed for licensure of such medical countermeasures. Methods Cynomolgus macaques (CMs) were challenged by intradermal (ID) inoculation or exposure to an aerosol containing CHIKV Ross strain at different target infectious doses (103–107 plaque forming units (PFU)). The clinical and virologic courses of disease were monitored up to 14 days post-exposure. Results ID infection of CMs led to overt clinical disease, detectable viremia, and increased blood markers of liver damage. Animals challenged by aerosol exhibited viremia and increased liver damage biomarkers with minimal observed clinical disease. All animals survived CHIKV challenge. Conclusions We have described CHIKV infection in CMs following ID inoculation and, for the first time, infection by aerosol. Based on limited reported cases in the published literature, the aerosol model recapitulates the virologic findings of human infection via this route. The results of this study provide additional evidence for the potential use of CMs as a model for evaluating medical countermeasures against CHIKV.